Sosialisasi Megathrust dan Simulasi Bencana Alam Gempa Bumi di SMP Negeri 1 Buluspesantren - Astutik, Dwi Retno; Iskahar, Iskahar; Susanti, Rini Puji (Universitas Pahlawan Tuanku Tambusai, 2025)
Kebumen Regency is one of the regencies in Central Java that borders the southern coast of Java and is traversed by the Indo-Australian megathrust plate boundary. Due to its high tectonic activity, it is highly susceptible to earthquakes. Socialization and simulation of disaster mitigation were conducted at SMP N 1 Buluspesantren, one of the coastal schools in Kebumen. The purpose of socialization and mitigation simulation is to provide education so that students are prepared to face natural disasters, especially earthquakes. The results of socialization and simulation for students of SMP N 1 Buluspesantren show that they have good knowledge of megathrust earthquakes, as indicated by the results obtained in the knowledge variable, which received a percentage of 81.4%, and in the disaster preparedness variable, students of SMP N 1 Buluspesantren showed good results with a score of 85.2%.